Identification of Measurement Variables for Understanding Vulnerability to Education Inequality in Developing Countries: A Conceptual Article. (May 2020) - Obasuyi, Folorunso Obayemi Temitope; Rasiah, Rajah; Chenayah, Santha
The article reviews the concept of vulnerability and develops a framework for vulnerability to education inequality (VEI). It further reviews the concept of education inequality and develops a framework for the cumulative measuring instruments of inequality of education. The schooling vulnerability processes are developed to understand the migration of susceptible children in susceptible compartment to tragedy compartment and later migrate to resilience compartment. For statistical testing, the article develops tangible hypotheses arising from the VEI framework. These theoretical hypotheses could serve as valuable guidelines for predicting the degree of susceptibility that triggers the prevalence of inequality of education among the school-age children. The findings show that the VEI framework contains various stimuli, arranged in cubicles, attributable to within-education (WE), socioeconomic status (SES), and school physical environmental (SPE) stimulus. Consequently, a VEI structural model (VEISM) is proposed, representing a structural equation framework that captures the latent and manifest indicators of the VEI cubicles. Because intervention was built into the VEI framework, the mediation and moderation effects are captured in the VEISM for examination. Nevertheless, further research should be concentrated on macroeconomic indicators, for example, sociopolitical instability, war and economic upturn risks that could trigger a school-age child been vulnerable to education inequality. Finally, susceptibility → tragedy → resilience discovered in the article, with epidemiological properties, requiring a further mathematical and epidemiological modeling.